To rate spread internal gravity waves - Ekaterina Gennadevna Nabrodova; Anastasiya Urevna Didenko; Robert Gurgenovich Zakinayn (Наука. Инновации. Технологии)
Sometimes mistakenly assumed that gravity waves only have a frequency equal to Brunt - Vaisala. However, there is a wide range of wave frequencies are less than this value. The frequency of oscillation vertically displaced from the equilibrium position of the air particles in a stably stratified atmosphere is equal to the frequency of Brunt - Vaisala. This resonance (on site) frequency vibrations in the air, and even if it were possible to imagine some process, which will cause vertical vibration with a frequency of greater than Brent frequency - Vaisala, this vibration will not be supported by the buoyancy of the atmosphere, and the vibration amplitude would decrease rapidly with the distance from the point of compulsion. Thus, the maximum frequency of the gravitational wave frequency equal to Brent - Vaisala, as there is a wide spectrum of waves whose frequencies are less than this value.